2014
DOI: 10.1002/pi.4697
|View full text |Cite
|
Sign up to set email alerts
|

Atom transfer radical polymerization as a powerful tool in the synthesis of molecular brushes

Abstract: Macromolecules with complex architectures such as molecular brushes (MBs) have received much attention over the last two decades. This interest is largely due to their potential applications in many fields, such as drug delivery and electronics, among others. The synthesis of such complex macromolecules can only be achieved via the use of controlled polymerization techniques such as atom transfer radical polymerization (ATRP). This review highlights the use of ATRP in the synthesis of MBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 135 publications
(205 reference statements)
0
27
0
Order By: Relevance
“…Atom transfer radical polymerization (ATRP) is proven to be one of the most versatile reversible deactivation radical polymerization (RDRP) methods that enables the preparation of polymers with controlled molecular weights (MWs), narrow molecular weight distributions (M w /M n , MWDs), and targeted degrees of polymerization (DP) [1][2][3][4][5][6][7][8][9][10][11][12][13]. The advent of low amount catalyst ATRP system, such as simplified electrochemically mediated ATRP (seATRP) [14] offers more environmentally friendly reaction conditions for the synthesis of polymers [15].…”
Section: Introductionmentioning
confidence: 99%
“…Atom transfer radical polymerization (ATRP) is proven to be one of the most versatile reversible deactivation radical polymerization (RDRP) methods that enables the preparation of polymers with controlled molecular weights (MWs), narrow molecular weight distributions (M w /M n , MWDs), and targeted degrees of polymerization (DP) [1][2][3][4][5][6][7][8][9][10][11][12][13]. The advent of low amount catalyst ATRP system, such as simplified electrochemically mediated ATRP (seATRP) [14] offers more environmentally friendly reaction conditions for the synthesis of polymers [15].…”
Section: Introductionmentioning
confidence: 99%
“…28,106,247,252 In addition to this, the Matyjaszewski and the Sheiko Groups showed that using additional quantities of the deactivator could improve the polymer brush by controlling the anticipated persistent radical effect. 223,247,265 The radicals can reversibly deactivate back to dormant polymer chains, which also means that the metal is reduced to the lower oxidation state. Table 2 shows a selection of the catalyst systems used in rest of this review.…”
Section: 263mentioning
confidence: 99%
“…This is important as it can reduce the amount of termination steps. 223,241 Due to the importance of ATRP in polymer brush development, it is further reviewed in the next section.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Atom transfer radical polymerization (ATRP) is one of the most rapidly developing areas of polymer science, allowing to obtain effective control over molecular weights (MWs), narrow molecular weight distributions (MWDs), architectures, and well-defined compositions [1][2][3][4][5][6][7][8][9]. However, normal ATRP has one significant limitation -it requires a large amount of the catalyst, which is sensitive to air and other oxidant.…”
Section: Introductionmentioning
confidence: 99%